2021
DOI: 10.1007/s40722-021-00204-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation and comparison of turbulence models for predicting wakes of vertical axis wind turbines

Abstract: Vertical axis wind turbine (VAWT) array design requires adequate modelling of the turbine wakes to model the flow throughout the array and, therefore, the power output of turbines in the array. This paper investigates how accurately different turbulence models using 2D computational fluid dynamics (CFD) simulations can estimate near and far wakes of VAWTs to determine an approach towards accurate modelling for array design. Three experiments from the literature are chosen as baselines for validation, with thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The power coefficient curve for the time step of 0.1°agrees well with the curve with the time step of 0.05°. Moreover, Sahebzadeh et al 78 for two VAWTs and previous studies for a single VAWT 73,79 showed that the time step of 0.1°provides accurate results. Therefore, in the current study, the azimuthal angle increment for all simulations is 0.1°; for the TSR of 2.63, the time step value will be 3.…”
Section: Physical Modelmentioning
confidence: 90%
See 1 more Smart Citation
“…The power coefficient curve for the time step of 0.1°agrees well with the curve with the time step of 0.05°. Moreover, Sahebzadeh et al 78 for two VAWTs and previous studies for a single VAWT 73,79 showed that the time step of 0.1°provides accurate results. Therefore, in the current study, the azimuthal angle increment for all simulations is 0.1°; for the TSR of 2.63, the time step value will be 3.…”
Section: Physical Modelmentioning
confidence: 90%
“…Also, by studying different turbulence models, Daróczy et al 72 introduced the SST kω $k-\omega $ model as one that performs well in VAWTs simulations. Also, Barnes et al 73 found that the commonly used SST kω $k-\omega $ model has satisfactory results and faster convergence. The SST kω $k-\omega $ model combines the kω $k-\omega $ model for the boundary layers and the kε $k-\varepsilon \,$model for the rest.…”
Section: Numerical Approachmentioning
confidence: 99%